(untitled) (Heritage, 2024)
Until the introduction of land registers at the end of 1934, the ownership of immovable property in Belgrade was proved through ownership documents, which were prepared by the Cadastral Department as a department of the Municipality of Belgrade. The book of ownership documents was a public record of immovable properties and real rights over them - ownership. At the beginning of the 30s of the ХХ century, records of real estate ownership were created in Belgrade. It was about ownership documents that were issued to the owners by the Belgrade Municipal Court. A total of 12,471 ownership documents were issued, 10 of which confirmed the ownership of the Serbian Royal Academy of Sciences. At the beginning of the 30s of the ХХ century, records of real estate ownership were created in Belgrade. It was about ownership documents that were issued to the owners by the Belgrade Municipal Court. A total of 12,471 ownership documents were issued, 10 of which confirmed the ownership of the Serbian Royal Academy of Sciences. Today, these ownership documents are kept in the Historical Archives of Belgrade. Ownership documents, as a presentation of archival materials, have been prepared in this work, with the aim of contributing to a broader picture of the arrangement of property-legal relations in Belgrade during the Kingdom of Yugoslavia. Since ownership documents contain information about the property of certain individuals, they can also be used for the prosopography of Belgrade. The ownership documents of the Serbian Royal Academy of Sciences were selected as a representative example due to the special national importance of this institution, which was renamed the Serbian Academy of Sciences and Arts after the Second World War.